The Impact of Technology-Based Games on The Fine Motor Development of Special Needs Children - Rukmini, Rukmini; Iswati, Iswati; Andriani, Dewi (STIKES Adi Husada, 2025)
The development of fine motor skills in children is a crucial ability that can be nurtured. The development of fine motor skills is frequently delayed in children with exceptional disabilities. Technology-based games, available in a variety of specialized smartphone applications, are one way to gradually and entertainingly improve children's fine motor skills. The purpose of this study is to assess the effectiveness technology-based games in helping children with special needs develop their fine motor skills. The research design uses a quasi-experimental method with a one-group pre-post test approach. A total of 28 children with special needs were the subjects of the study. Data were collected through observation using the Bender Visual Motor Gestalt Test instrument and analyzed using the Wilcoxon statistical test. The research results show that after engaging in technology-based games, the percentage of those surveyed with high fine motor abilities rose from 21.4% to 57.1% after playing technology-based games. Statistical test analysis showed a significant improvement in the fine motor skills of children with special needs after being given technology-based games, with a p-value of 0.000 and α < 0.05. The results of this study provide evidence of the influence of technology-based games on fine motor skills in special needs children. The implications of the research on technology-based games can be an effective alternative for developing fine motor skills in special needs children.